Victor's memory: Sri Lanka's post-war memoryscape in comparative perspective. Issue 1 (2nd January 2020) - McCargo, Duncan; Senaratne, Dishani
ABSTRACT: How are victims of civil wars and conflicts remembered in the context of an illiberal peace? When a violent conflict is ended by the use of overwhelming state force, without benefit of a political process, the victors may seek to control the ways in which the violence is memorialised; while in a war where the insurgents remain in the shadows, public recognition of their losses may be impossible. Using Thailand as a comparison, this study compares the configuration of conflict memorialisation in Sri Lanka, focusing on two Tamil communities where Catholic priests played important roles: Vankalei and Mullivaikkal. In both cases, the Sri Lankan military saw memorialisation as a threat to national narratives about the rights and wrongs of the conflict. Yet in neither case have local people addressed the human rights abuses committed by the LTTE: their narratives emphasise victimhood and evade discussion of agency. Memorials dedicated to those who perished during civil conflicts are likely to be one-sided. Accordingly, the paper argues that an illiberal peace poses particular challenges for historical memory and memorialisation.